Evidence of widespread pollen limitation in diverse specialty crops on commercial farms - Eleanor Stroh; Ashley Leach; Zeus Mateos-Fierro; Ian Kaplan (Royal Society Open Science)
Specialty crops (non-staple fruits and vegetables) have diverse pollination requirements and pollinator communities, yet production may be limited by pollen limitation. We quantified insect pollination and pollen limitation on commercial farms across crops that differ in their reliance on insect pollination, including watermelons, apples, blueberries and tomatoes. We also considered the impact of thinning in apples and protected culture of tomatoes on pollination dynamics. We compared fruit set and quality across insect exclusion, open pollination and hand pollination treatments. Insect pollination increased fruit set in every crop (increase from exclusion to open treatments; mean = 22.9%, range = 1.1–48.0%), while hand pollination increased fruit set across crops, except for apples after thinning (increase from open to hand pollination treatments; mean = 5.8%, range = 0.3–8.7%). The effect of pollination treatment on fruit quality varied. Field tomatoes were the only crop to demonstrate pollen limitation in all metrics. Despite evidence for ambient pollinator contributions across specialty crops, our work highlights the opportunity for further increases in yield, particularly in crops not considered dependent on pollinators like tomatoes.